2017
DOI: 10.1128/aac.01106-16
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of Novel Azole Compounds ATTAF-1 and ATTAF-2 against Fluconazole-Susceptible and -Resistant Isolates of Candida Species

Abstract: The in vitro activities of two novel azole compounds (aryl-1,2,4-triazol-3-ylthio analogues of fluconazole [ATTAFs]) and five comparator antifungal agents against 52 clinical Candida isolates from 5 different species were determined. The novel azole compounds had the lowest geometric mean MICs, followed by fluconazole. Moreover, combinations of these compounds with fluconazole exhibited synergistic effects against fluconazole-susceptible (22 of 23 isolates), fluconazole-susceptible dose-dependent (10 of 13 iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…Fluconazole is a fungistatic antifungal drug commonly used in the treatment of Candida infections, presenting an effective spectrum of activity against these pathogens (Mushi et al, 2018). Recently, studies involving newly azole base compounds (Motahari et al, 2018; Mahmoudi et al, 2019) and combination therapy (Fakhim et al, 2017) demonstrate its antifungal activity against C. albicans and non C. albicans species. However, due to its frequent use, fluconazole resistant strains have emerged (Akins, 2005; Morschhäuser, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Fluconazole is a fungistatic antifungal drug commonly used in the treatment of Candida infections, presenting an effective spectrum of activity against these pathogens (Mushi et al, 2018). Recently, studies involving newly azole base compounds (Motahari et al, 2018; Mahmoudi et al, 2019) and combination therapy (Fakhim et al, 2017) demonstrate its antifungal activity against C. albicans and non C. albicans species. However, due to its frequent use, fluconazole resistant strains have emerged (Akins, 2005; Morschhäuser, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These results confirmed that RF3 exerted antifungal activities by disrupting membrane integrity. Compared with other kinds of novel antifungal agents that are designed base on the structure of FLU ( Fakhim et al, 2017 ), this non-specific physical membrane-disrupting mechanism of RF3 reduced the development of antifungal resistance. Studies indicate that ROS production is involved in antifungal mechanisms of certain peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Within the same line azole-like molecules have also been obtained showing increased antifungal potency against all Candida species, compared to the efficacy exhibited by fluconazole [143]. These modified azoles, named ATTAF-1 and ATTAF-2, share general structural features with triazole alcohols, however, their mode of action appears to differ from the one of fluconazole which is an important trait to sensitize resistant strains [143]. Further on, Shrestha et al (2017) developed a series of 27 alkylated variants of fluconazole, some of which presented a low hemolytic activity, low cytotoxicity and strong inhibitory potential against several Candida species [144].…”
Section: Redesign Of "Old Antifungals"mentioning
confidence: 90%
“…The most paradigmatic examples are the new formulations of amphotericin B, which include lipid-associated and liposomal formulations showing higher fungal targeting and reduced toxicity against the host [142]. Within the same line azole-like molecules have also been obtained showing increased antifungal potency against all Candida species, compared to the efficacy exhibited by fluconazole [143]. These modified azoles, named ATTAF-1 and ATTAF-2, share general structural features with triazole alcohols, however, their mode of action appears to differ from the one of fluconazole which is an important trait to sensitize resistant strains [143].…”
Section: Redesign Of "Old Antifungals"mentioning
confidence: 99%